A review on discoloration and high accelerated testing of optical materials in LED based-products. (February 2018) - Yazdan Mehr, M.; Toroghinejad, M.R.; Karimzadeh, F.; van Driel, W.D.; Zhang, G.Q.
Abstract: Reduction of intensity of light output is one of the most common degradation modes in light-emitting diode (LED) systems. It starts from the failure of the various components in the system, including the chip, the driver, and optical components (i.e. phosphorous layer). The kinetics of degradation in real life applications is relatively slow and in most cases it takes several years to see an obvious deterioration of optical properties. Highly Accelerated Stress Testing (HAST) set-up and a methodology to extrapolate the results to real time applications are therefore needed to test the reliability of LED packages and lens materials. Using HAST concept in LED industry is inevitable due to the necessity of assessing the reliability of new products in a short period of time. This paper aims at briefly clarifying the degradation mechanisms of optical components in LED packages and explaining how they contribute to the depreciation of light output of the LED systems. The concept of HAST and the way the reliability of LED packages can be evaluated will also be discussed.